Integrated Modeling of Minerva Medica to Identify the Dynamic Effects of Rail-Traffic Vibrations - Santini, Silvia; Sabbatini, Valerio; Sebastiani, Claudio; Baggio, Carlo (Buildings (Basel), 2023)
A comprehensive study was carried out to integrate information from different sources and evaluate the effects of induced vibrations on a temple. Historical analysis was fundamental to interpreting the evolution of the construction and defining the HBIM. Experimental data were implemented in the FEM of the site, including the temple, its foundations, and the soil stratifications. Sensitivity analysis was carried out to identify the most influential parameters, which were calibrated to reduce error with the experimental frequencies. The FEM was further optimized with the Douglas–Reid method, considering, simultaneously, modal frequencies and deformations. Two different nonlinear dynamic analyses were performed; one analysis studied the effect on the temple of the dynamically moving load of the tram, and the other analysis studied the response of the temple to three-dimensional accelerations applied at the base. The drawbacks of each simulation were identified by comparing the numerical and experimental results.